The Relationship Between Serum miRNAs and Surgical Prognostic Factors in Gastric Cancers - Çağrı Büyükkasap; Engin Küçükdiler; Mahir Nasirov; Niyazi Samet Yılmaz; Hasan Dağlı; İlke Önen; Furkan Aydoğdu; Aydın Yavuz; Hüseyin Göbüt; Asiye Uğraş Dikmen; Kürşat Dikmen; Hasan Bostancı; et al. (Gazi Medical Journal)
Objective: There is a continued need for biomarkers for patients with gastric cancer that can aid in diagnosis, treatment follow-up, and relapse detection. The objective of this study was to investigate the role of serum microRNA (miRNAs) in diagnosing gastric cancer and their relationship with prognostic factors that impact the choice of surgical approach. Methods: We compared the serum miRNA expression levels of 35 patients who underwent gastrectomy and D2 lymph node dissection for gastric adenocarcinoma between 2015-2018 with those of 33 controls. We also evaluated the relationship between serum miRNA expression levels and pathological prognostic factors. Results: The serum levels of miR-17-5p, miR-21-5p, miR-27a-3p, miR-146a-5p, miR-148a-3p, and miR-203a-3p were significantly higher in gastric cancer patients. In early gastric cancer patients, serum levels of miR-21-5p, miR-27a-3p, miR-106b-5p, miR-146a-5p, and miR-148a-3p levels were significantly higher. Furthermore, serum levels of miR-106b-5p and miR-146a-5p were associated with tumor localization [area under the curve (AUC): 0.773, 0.797; p=0.049, 0.036], while serum levels of miR-27a-3p and miR-148a-5p were associated with the T-stage of the tumor (AUC: 0.748, 0.729; p=0.036, 0.049). Conclusion: Serum levels of miR-17-5p, miR-21-5p, miR-27a-3p, and miR-203a-3p were found to be diagnostic biomarkers in gastric cancers. The expression levels of serum miR-106b-5p and miR-146a-5p were found to be related to tumor location, whereas the expression levels of serum miR-27a-3p and miR-148a-5p were found to be related to the T-stage of the tumor. These findings can impact the surgical approach for gastric cancer patients.